Tree-Ring Isotopic Records Suggest Seasonal Importance of Moisture Dynamics Over Glacial Valleys of the Central Himalaya - Singh, Nilendu; Shekhar, Mayank; Parida, Bikash Ranjan; Gupta, Anil K.; Sain, Kalachand; Rai, Santosh K.; Bräuning, Achim; Singh Charkaborty, Joyeeta; Sharma, Vikram; Kamal Tiwari, Reet; Chauhan, Pankaj; Montagnani, Leonardo (Frontiers in Earth Science, 2022)
Accelerated glacier mass loss is primarily attributed to greenhouse-induced global warming. Land–climate interactions have increasingly been recognized as an important forcing at the regional-local scale, but the related effects on the Himalayan glaciers are less explored and thought to be an important factor regulating spatial heterogeneity. The aim of the present study is a multi-decadal approximation of glacier – hydroclimate interaction over the western region of the central Himalaya (WCH). Multi-species, highly coherent, tree-ring cellulose δ18O chronologies from three sites across the WCH were used to derive atmospheric humidity (Atmospheric Moisture Content: AMC) record of the last four centuries. Coherency analyses between regional AMC and glacier mass balance (GMB) indicate an abrupt phase-shift after the 1960s within a common record of the last 273 years. To ascertain the cause of this phase-shift, annual AMC was disintegrated into seasonal-scale, utilizing ~200 years of δ18O record of a deciduous tree species. Seasonal (winter-accumulation: Oct–Mar; summer-accumulation: Apr–Sep) AMC reconstructions and decomposition results indicate a higher sensitivity of regional ice-mass variability to winter moisture dynamics than summer. Over the last two centuries, the relationship between GMB and summer season AMC varied insignificantly. However, despite a decline in Indian summer monsoon (ISM) precipitation after the mid-20th century, the summer season AMC – GMB relation remained stable. We hypothesize that decadal-scale greening, and consequent increased evapotranspiration and pre-monsoon precipitation might have been recycled through the summer season, to compensate for the ISM part of precipitation. However, isotope-enabled ecophysiological models and measurements would strengthen this hypothesis. In addition, high-resolution radiative forcing and long-term vegetation trends point towards a probable influence of valley greening on GMB. Our results indicate that attribution of ice-mass to large-scale dynamics is likely to be modulated by local vegetation changes. We contend that glacier-climate models that account for these processes and feedbacks could reliably improve projections.